Removal of toxic metals from aqueous solution by duckweed (Lemna minor L): Role of harvesting and adsorption isotherms - Hasar, H; Obek, E (Springer Heidelberg, 2001)
The sorption of Cr(VI), Cu(II) and Cd(II) ions from aqueous solutions into duckweed has been investigated. Three reactors have been used in the experimental studies. Whereas duckweed was not harvested in the first reactor, it was harvested once every four days and once every two days in the second and the third reactors, respectively. The detention time was 8 days. For all the metal ions, the results show that heavy metals can be successfully removed from solutions if duckweed is frequently harvested. When duckweed was harvested every two days, while, for initial concentrations of 5 mg l(-1), Cr(VI) ions were measured at 0.5 mg l(-1) and the levels of Cu(II) and Cd(II) were not detectable, for initial concentrations of 10 mg l(-1), final concentrations were: Cr(VI) 0.90; Cu(II) 0.94; and Cd(II) 2.10 mg l(-1). In the isotherm studies, the Langmuir and Freundlich constants have been calculated for the results obtained during the detention time of four days in the second reactor. The experimental adsorption data fitted reasonably well the Freundlich isotherm.
Keywords: duckweed; harvesting; removal; sorption; heavy metal; Langmuir; Freundlich